3D micro-porous conducting carbon beehive by single step polymer carbonization for high performance supercapacitors: the magic of in situ porogen formation - Puthusseri, Dhanya; Aravindan, Vanchiappan; Madhavi, Srinivasan; Ogale, Satishchandra (Energy & Environmental Science, 2014)
We report non-templated synthesis of interconnected microporous carbon (IMPC) sheets having beehive morphology by direct pyrolysis of poly(acrylamide-co-acrylic acid) potassium salt in inert atmosphere without any activation. The presence of the alkali metal in the selected polymer precursor results in a high specific surface area of 1327 m(2) g(-1). Importantly, 80% of the pore volume is contributed by micropores with pore size ranging from 1-2 nm which is ideal for use as an electrode for supercapacitors. Whereas the rest of the surface area was contributed by a small fraction of mesopores and macropores due to the interconnected structure. The presence of three different types of pores make the material ideal for supercapacitor electrodes. IMPC was tested as an electrode in both aqueous and non-aqueous supercapacitors. All the aqueous measurements were done in 1 M H2SO4 solution with a potential window 1 V. A specific capacitance of 258 F g(-1) was realized at a constant charge-discharge current of 0.5 A g(-1) and it maintained at a value of 150 F g(-1) at 30 A g(-1). A long cycle stability of 90% capacitance retention was observed after 5000 charge-discharge cycles at a current density of 2 A g(-1). At the highest power density 13 600 W kg(-1) the energy density was found to be 3.1 W h kg(-1). Non aqueous performance was tested in the presence of 1 M LiPF6 in ethylene carbonate-di-methyl carbonate with 5 mg active material loading. A specific capacitance of 138 F g(-1) was obtained at a current density of 0.25 A g(-1) and it retained at a value of 100 F g-1 at 10 A g(-1). The material can deliver an energy density of 31 W h kg(-1) at its highest power density of 11 000 W kg(-1) in a two electrode system based on active material loading.